Microsoft office Visio 2007 inside out - Walker, Mark H. (Microsoft Press, 2007)
Learn everything you need to know for working with Microsoft Office Visio 2007--from the inside out! This book packs hundreds of time-saving solutions, troubleshooting tips, and workarounds for using Office Visio 2007--all in concise, fast-answer format. Whether you are upgrading from Office 97 or Office 2003, you'll be able to dig in to the work-ready resources that help you take your Visio 2007 experience to the next level. This information-packed complete reference shows you how to get the most out of Visio 2007 and find out what's new. You will learn how to create diagrams and use them in other Office programs, how to create timelines and PERT charts to track projects and scheduling tasks, and how to use CAD drawings in Visio. In addition, you will explore how to use Visio to create technical diagrams for mechanical, electrical, and process engineering, and more. Plus, you'll get an easy-to-use companion CD packed with custom resources and a fully searchable eBook. With INSIDE OUT, you get all muscle and no fluff!